RANCANG BANGUN SISTEM KEAMANAN RUMAH DENGAN FACE RECOGNITION BERBASIS ESP32-CAM - Diki Anugrah Pratama; Muhamad Bahrul Ulum (Jurnal Komputasi, 2024)
Crimes and criminal activities continue to occur relentlessly. Criminal actions violate the laws of the state, religious norms, and social standards, resulting in economic and psychological losses. This research proposes the design of a Face Recognition-based security system using ESP32-CAM. This system functions as a facial recognition device and performs facial data verification stored on the ESP32-CAM microcontroller [1]. The system is capable of detecting verified faces and issuing warnings if an unknown face is detected by the ESP32-CAM microcontroller device. The design of this security system utilizes the ESP32-CAM as the microcontroller, an OV2640 camera, and a USB to TTL connection for linking the ESP32-CAM to the computer via the USB port. The design and creation of this device are implemented through the Arduino IDE program and displayed via the WebSocket Arduino ESP32-CAM [2].